2005
DOI: 10.1097/01.mlg.0000163766.66223.97
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial Resection for Nonmelanoma Skin Cancer of the Head and Neck

Abstract: Acceptable mortality and morbidity is possible using craniofacial resection to treat advanced nonmelanoma skin cancer. Although disease-specific survival remains poor, positive trends were noted in local control beginning at 2 years of follow-up. Because patients often have few remaining options for cure, craniofacial resection is justified when technically feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 16 publications
(43 reference statements)
1
25
1
Order By: Relevance
“…Furthermore, published literature to date does not specifically focus on NMSCs with intracranial extension. 1,9 Hence, the role of surgery and the extent to which it should be pursued in light of intracranial and/or cranial nerve invasion is unclear due to the relative lack of evidence on this subject. We currently pursue resection in patients who meet the following criteria: lack of major medial comorbidities, high performance status, lack of major vessel (arterial or venous) involvement, absence of lower cranial nerve involvement, lack of extensive or eloquent brain invasion, and presence of only local disease at presentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, published literature to date does not specifically focus on NMSCs with intracranial extension. 1,9 Hence, the role of surgery and the extent to which it should be pursued in light of intracranial and/or cranial nerve invasion is unclear due to the relative lack of evidence on this subject. We currently pursue resection in patients who meet the following criteria: lack of major medial comorbidities, high performance status, lack of major vessel (arterial or venous) involvement, absence of lower cranial nerve involvement, lack of extensive or eloquent brain invasion, and presence of only local disease at presentation.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported our experience with a cohort of 35 patients who underwent surgery from 1982 through 1993. 1 In light of surgical advancements and shifts in adjuvant therapy protocols, we reviewed our experience from 1994 through 2012; primary outcomes assessed were overall survival (OS), progression-free survival (PFS), and short-term surgical outcomes.…”
mentioning
confidence: 99%
“…Occasionally, skin cancers may be exceptionally aggressive, invading deeper anatomical planes and destroying soft tissues, bone and even the dura mater and brain. Some authors have recently reported their experience with skin carcinomas with skull base involvement [3] . In some published Brazilian skull base surgery series, they represent the main histological types of tumor [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Perineural invasion has been considered an ominous prognostic factor in skin carcinomas [3,[8][9][10][11][12] , especially when this invasion was detected by clinical and/or radiological findings [11,13,14] .…”
Section: Introductionmentioning
confidence: 99%
“…(Backous, DeMonte et al 2005). Backous used as contraindication criteria for this type of resection encasement of the carotid artery or optic chiasm, cavernous sinus invasion or distant metastasis.…”
Section: Treatment Of Primary Tumormentioning
confidence: 99%